Trends and advances in Leptospira, a bibliometric analysis - Wang, Wei; Gao, Yamin; Ji, Jianyu; Huang, Zhai; Xiong, Bin; Xiang, Shulin (Frontiers in Microbiology, 2025)
BackgroundLeptospirosis is an acute zoonotic disease caused by pathogenic Leptospira, primarily transmitted to humans through contact with water or soil contaminated by the bacteria. It is globally distributed, with heightened prevalence in tropical regions. While prior studies have examined the pathophysiology, epidemiology, and risk factors of leptospirosis, few have explored trends and emerging topics in the field. This study applies bibliometric analysis to generate a visual knowledge map, identifying research hotspots and forecasting future trends in leptospirosis investigations.MethodsData were extracted from the Web of Science Core Collection (WOSCC), encompassing all publications up to May 1, 2024. CiteSpace and VOSViewer software were used to analyze annual publication trends, as well as contributions from countries, institutions, journals, authors, references, and keywords, thereby pinpointing current research priorities and potential future directions.ResultsA total of 5,244 articles were included, sourced from 4,716 institutions, 955 journals, and 156 countries or regions. The United States led with 1,315 publications and had the most significant influence in the field. “PLOS Neglected Tropical Diseases” published the highest number of articles (166), while “Infection and Immunity” garnered the most citations (6,591). Prominent research areas included restriction endonucleases, monoclonal antibodies, outer membrane proteins, water environments, detection methods, and antimicrobial agents. Research focus has shifted from early genomic and antigenic studies to investigations into outer membrane protein functions and environmental persistence, culminating in recent advances in molecular mechanisms and diagnostic technology development.ConclusionThis bibliometric analysis provides a comprehensive snapshot of leptospirosis research, emphasizing collaborations and impact among authors, countries, institutions, and journals. It offers valuable insights into ongoing trends and serves as a reference for future collaboration and research opportunities in the field.